A UK Perspective on Pain and Atypical Performance - When the Maths doesn't Add up!. (1st June 2022) - Hall, V.
Abstract : This presentation provides an overview of factors that can cause symptom exaggeration and/or fabrication in chronic pain. It will explore how symptom and performance validity tests can be applied to chronic pain in the context of a malingering framework and the problems of implementing this in the UK through a case example. Disclosure: No significant relationships.